Management Analysis of Logistics Management Pharmacy and Health Supplies in Bandar Khalipah Community Health Center - Syahrani, Putri; Hasibuan, Rafiqoh; Pohan, Rahmaidah; Aisyah, Siti Nur; Wulandari, Tri (PROMOTOR, 2025)
Drug management is a series of activities aimed at ensuring the availability of appropriate and sufficient drugs for the community. These activities include planning, procurement, storage, distribution, and destruction of drugs. The purpose of this study was to understand in depth how the management of pharmaceutical and health supplies logistics is carried out at the Bandar Khalipah Health Center. The results of the study indicate that planning, procurement, storage, distribution, use, and evaluation of drugs at the Bandar Khalipah Health Center require a systematic process and involve many parties to ensure the availability of sufficient and appropriate drugs. The researcher suggests that to improve the management of pharmaceutical supplies at the Bandar Khalipah Health Center, several steps that can be taken are to improve the drug storage system by expanding space or using technology to monitor drug stock.